Cultural capital competencies of teachers in sports education: A mixed-method study - Karakaya, Yunus Emre; Bingolbali, Abdullah; Sahin, Aykut (Sciendo, 2022)
Study aim: In this study, the cultural capital competencies of physical education and sports teachers were investigated using the mixed method (quantitative and qualitative) research design. Material and methods: The participants of the quantitative method were 248 physical education and sports teachers working in educational institutions in Turkey, and 24 volunteers from this group were randomly selected for the qualitative phase. The analysis of the data was performed using SPSS 22.0 and QSR NVIVO-10 software. The Cultural Capital Scale was utilized to collect the quantitative data, while the qualitative data was obtained through two semi-structured open-ended questions. Results: The findings of the study revealed no significant differences in the variables of gender, education level and the type of location where the teacher grew up. A positive and high level of correlation was found between the Cultural Capital Scale and the subscale Intellectual Accumulation. The Intellectual Accumulation subscale was found to explain 87% of the variance of the Cultural Capital Scale (R-2 = 0.872). Conclusions: Creating educational environments where intellectual accumulation, participation, cultural awareness, and cultural potential dimensions are considered at every stage of education is suggested to enrich the cultural capital accumulations of physical education and sports teachers.
Keywords: Cultural Capital; Teacher; Physical Education; Sports